Running-Related Musculoskeletal Injuries in Saudi Arabia: Epidemiology, Biomechanical Determinants, and Global Comparative Insights - Marwan M. A. Aljohani (Healthcare, 2026)
Background/Objectives: Running is widely promoted for its health benefits, but it is also associated with a substantial burden of musculoskeletal injuries, particularly affecting the lower extremities. In Saudi Arabia, participation in recreational running has increased substantially in recent years. This review synthesizes global evidence on running-related musculoskeletal injuries and critically examines its applicability to the Saudi context, with emphasis on regional evidence gaps and research priorities. Methods: A narrative literature search of PubMed/MEDLINE and Scopus was conducted from database inception to August 2026 using predefined search concepts and eligibility criteria related to running, musculoskeletal injury, biomechanics, training load, and Saudi Arabia, with reporting guided by the SANRA criteria for narrative reviews. Results: Global evidence indicates that running-related injuries reflect complex interactions among training load, biomechanics, tissue capacity, and environmental factors. Injury prevalence and incidence vary considerably across studies because of methodological heterogeneity, although novice runners generally experience greater injury risk and the knee, lower leg, ankle, and foot are frequently affected. Saudi runner-specific evidence remains limited, with much of the available regional literature derived from cross-sectional, self-reported, or broader physically active populations. Conclusions: In Saudi Arabia, runner-specific injury data remain limited. Existing studies mainly concentrate on general physically active populations and lack standardized injury definitions, exposure-adjusted incidence measures, and prospective designs. Future research should prioritize prospective biomechanical surveillance using wearable sensor technology to capture real-world running mechanics and training loads.